Analisis Prilaku Konsumen, Produsen dan Pasar dalam Ekonomi Islam - Tiara Nur Fasiatul Zannah (Civiliza Publishing, 2020)
Abstract. Islamic economics is a science that studies human economic behavior whose behavior is regulated based on Islamic religious rules. As Muslims, it is necessary to follow economic behavior which is regulated by Islam. As has been explained in the Al-Quran or hadith about how Muslims should behave as producers, consumers, and as owners of capital. Consumer behavior is part of marketing management that deals with humans as target markets. The behavior of consumers with one another is not the same and changes every time, so consumer behavior in buying must be studied continuously, given the increasingly competitive market competition conditions. Therefore, the researcher wants to study the consumer behavior of staple and non-staple goods, namely for the staple goods of rice and sugar and for non-staple ground coffee and canned milk